Development of PCR assay for targeting partial lipL21 and lipL41 gene of leptospira - Chandan, S; Umesha, S; Bhure, SK; Haraprasad, N; Chandrashekar, S (Nepal Journal of Biotechnology, 2010)
Leptospirosis is a bacterial zoonotic disease caused by spirochetes of the genus Leptospira that affects human and a wide range of animals. The direct method of diagnosis of leptospirosis, has been so far by culture isolation but it is time consuming and potentially biohazardous. Another traditional method is the detection of antibodies (Serological tests) which is also a time consuming method and fails to identify the infecting serovar. To overcome these limitations associated with the cultivation and serology, we developed PCR assay targeting partial lipL21 gene and lipL41 gene of Leptospires using in-house designed P28/29 and P30/31 primers, with a product size of 385bp and 427bp. The amplicons were subjected to restriction enzyme digestion using RsaI, Pvu II and HindIII for product of P28/29 and ClaI, TaqI and RsaI were used for product of P30/31. The protocols were standardized and the assay targeting the partial lipL21 and lipL41 gene was found to be specific for eight pathogenic Leptospires out of nine leptospires tested. The products were then cloned in pGEMT Easy vector and sequenced to facilitate further studies. PCR could detect the target bacterial gene without any ambiguity and showed good efficiency in detection of targeted species in the sample. This simple, rapid and cost-effective method can be applicable in a prediction system to prevent disease outbreak by these Leptospira species and can be considered as an effective tool for disease diagnosis of Leptospira species. Key words: PCR; lipL21; lipL41; Molecular Diagnostics; Transformation. Nepal Journal of Biotechnology. Jan. 2011, Vol. 1, No. 1 : 22-30